Parents’ Experiences of Occupational Therapy for Children with Autism Spectrum Disorder - Md Saleh, Hazirah; Sultan Ibrahim , Syamsul Anwar; Vetrayan, Jayachandran (Environment-Behaviour Proceedings Journal, 2025)
Parents play a vital role in shaping occupational therapy (OT) outcomes for children with autism spectrum disorder (ASD), yet their experiences remain underexplored. This qualitative study at WQ Park Health and Rehabilitation Centre used Interpretative Phenomenological Analysis (IPA) to investigate parental perspectives. Semi-structured interviews with ten parents of children with mild ASD revealed three key themes: balancing hopes with therapy realities, fostering trust and collaboration with therapists, and overcoming systemic barriers such as cost and accessibility. Findings emphasize the importance of family-centered, collaborative OT practices that empower parents, enhance understanding, and ensure continuity of care beyond child-focused outcomes.